Perlindungan Konsumen Atas Hak Penggantian Kerugian - Jelang Fajar Putra Perdana; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
This study aims to analyze the compensation right of consumers from LA City Apartment who developed by PT. Priority Land Indonesia as a business actor. This research method is normative legal research with prescriptive of the study. The research approach used a law related to consumer protection over the compensation right as stated in the Consumer Protection Law. The type of data used primary and secondary data. Data collection techniques in this research used a library study with a deductive analysis. This research concludes that consumer protection for compensation rights in accordance with the sale and purchase agreement of LA City Apartment units should only be material but in resolving disputes that are taken through civil law in a material and immaterial because they did not use the Consumer Protection Law.